414 Are Lumbar Drains Necessary in Endoscopic Transellar Surgery with an Intraoperative High Flow Leak? a Systematic Review. (19th August 2022) - Pak, HYV; Hayhurst, C; Taylor, P
Abstract: Aim: Perioperative lumbar drains have been used to facilitate healing of the dura and prevent postoperative cerebrospinal fluid (CSF) leaks. However, the use of perioperative lumbar drains is controversial and has primarily been left to the surgeon's preferences. Through the use of meta-analysis, we aim to find out whether lumbar drains effectively reduce the risk of postoperative CSF leak in the context of a high flow intraoperative leak. Method: A systematic review was conducted using PRISMA guidelines. Databases used in literature searching include PubMed, Ovid (including Embase and Medline), Scopus and Cochrane Library. Articles published in 2006 or later were searched. The random-effects model was used in statistical analysis. Results: A total of 2623 articles were identified. After screening and full-text reviews, 21 studies were included. From the quantitative data analysis, lumbar drains did not significantly lower the rates of postoperative CSF leaks. In addition, lumbar drains were associated with complications as well as a lengthier hospital stay. Conclusions: Modern and rigorous repair techniques after endoscopic transsellar surgery are sufficient, and the use of lumbar drains is not necessary.